The Influence of the Discovery Learning Model with Socio-Scientific Issues Context on Scientific Literacy Skills and Cognitive Learning Outcomes - Mumtazah, Ziyana; Wahyuni, Tutik Sri; Silfianah, Ifah (J-PEK (Jurnal Pembelajaran Kimia), 2024)
Applying the learning model should encourage students to learn actively, think, and use their abilities to discover. Apart from that, learning linked to the SSI context can also support functional scientific literacy skills. StudyThis aims to analyse the influence of the discovery learning model in the context of Socio Scientific Issues (SSI) on students' scientific literacy abilities and cognitive learning outcomes on Basic Laws of Chemistry material. This research uses a quasi-experiment method with a control posttest-only group design—research population of class X students at MAN 10 Jombang. Sampling used the purposive sampling technique, which consists of two classes: the experimental class, which applies the SSI-based discovery learning model, and the control class, which uses discovery learning. Data collection used a 10-item essay test instrument to measure scientific literacy skills and a 15-item multiple choice test to measure cognitive learning outcomes. Both have been validated; the reliability was 0.869 and 0.889, respectively—data analysis using a t-test. The results of the research show that there is an influence of the SSI-based discovery learning model on scientific literacy skills with a 2-tailed sig value of 0.031 80,56.